1991
DOI: 10.1111/j.1365-2621.1991.tb04766.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion Variables on Cassava Extrudates

Abstract: Cassava flour was extruded by varying parameters of feed moisture; temperature; screw speed and feed rate. We investigated significance of each variable and interactions between variables on each extrudate characteristic. Optimum expansion (2.82) was at 11% feed moisture 120-125 "C; screw speed, 520rpm; feed rate, 250g/min. Effect of feed moisture was most significant on expansion, bulk density and extrudate moisture. Increasing temperature, increased expansion and water solubility, but decreased bulk density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
50
4
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 8 publications
19
50
4
3
Order By: Relevance
“…However, increasing moisture content had insignificant effects on WAI and WSI (P≥0:05). This is in contrast to the study by Njoki and Faller (2001) who reported that WAI and WSI decrease with decreasing moisture content; whereas Badrie and Mellowes (1991) observed an increase in WAI and decrease in WSI with increasing moisture content. The differences observed here could be attributed to the nature of the raw materials and the extrusion conditions.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…However, increasing moisture content had insignificant effects on WAI and WSI (P≥0:05). This is in contrast to the study by Njoki and Faller (2001) who reported that WAI and WSI decrease with decreasing moisture content; whereas Badrie and Mellowes (1991) observed an increase in WAI and decrease in WSI with increasing moisture content. The differences observed here could be attributed to the nature of the raw materials and the extrusion conditions.…”
Section: Resultscontrasting
confidence: 56%
“…This leads to increased moisture content of the melt and causes the amylopectin molecular structure to soften and its elastic characteristics to reduce leading to a decrease in SEI (Alvarez-Martinez et al 1988). An increase in feed moisture also causes a reduction in barrel temperature thereby creating a lower vapour pressure in the melt and resulting in less flashing of moisture and a reduced SEI (Badrie and Mellowes 1991). The trapped steam instead condenses in the extrudate on cooling and is responsible for the higher extrudate moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…Já o componente b* e a DCO entre farinha extrusada e não extrusada aumentaram com a redução da umidade. Neste caso, o baixo conteúdo de umidade durante o processamento da farinha de batata-doce favoreceu a ocorrência de reações de escurecimento não enzimáti-co. Segundo BADRIE & MELLOWES [6], a elevação da temperatura aumenta a intensidade da cor e altos níveis de umidade resultam em produtos mais claros, pois o aumento da umidade reduz o tempo de residência, proporcionando menor escurecimento não enzimático dos produtos extrusados.…”
Section: Embora Tenha Havido Variação Nos Valores Deste Atri-unclassified
“…Segundo BADRIE & MELLOWES (1991), a elevação da temperatura aumenta a intensidade da cor, e os altos níveis de umidade resultam em produtos Ciência Rural, v.40, n.6, jun, 2010. mais claros, pois o aumento da umidade reduz o tempo de residência, proporcionando menor ocorrência de caramelização e reação de Maillard.…”
Section: Resultsunclassified